MONITORING OF ANTIBIOTIC-RESISTANT BACTERIA IN THE TERRITORY OF UZBEKISTAN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Antibiotic resistance has emerged as one of the most critical global health issues of the 21st century, posing a serious threat to the effectiveness of current antimicrobial therapies. The increasing prevalence of antibiotic-resistant bacteria in Uzbekistan highlights the urgent need for continuous and systematic monitoring. This study provides a comprehensive review of the current status of antibiotic resistance surveillance in Uzbekistan, examining the main bacterial pathogens, mechanisms of resistance, and factors contributing to their spread. The analysis demonstrates that the overuse and misuse of antibiotics in both human medicine and agriculture, combined with limited laboratory diagnostic capacity and weak antibiotic stewardship, have accelerated the emergence of multidrug-resistant organisms such as Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, and Pseudomonas aeruginosa. The review further compares Uzbekistan’s monitoring capacity with international standards, including the WHO Global Antimicrobial Resistance Surveillance System (GLASS). The study emphasizes the importance of developing a national, AI-assisted surveillance platform to collect, analyze, and visualize resistance data in real time. Strengthening microbiological laboratories, promoting rational antibiotic use, and implementing nationwide education programs for healthcare professionals are essential for mitigating resistance. Establishing a unified data network across regions of Uzbekistan could become a cornerstone for evidence-based public health decisions and global collaboration in the fight against antimicrobial resistance.